Tingkat Penguasaan Mekanika Teknik Dikaitkan Dengan Prestasi Belajar Mahasiswa Pada Mata Kuliah Bidang Hidrolika Pada Prodi Teknik Sipil Fakultas Teknik Universitas Negeri Manado - Tulaka, Titof (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to obtain empirical data regarding the relationship between the level of mastery of engineering mechanics and student learning achievement in hydraulics courses in the Civil Engineering study program, Faculty of Engineering, Unima. This research research is classified as a descriptive method which is correlational because the aim is to detect the extent of the relationship between the level of mastery of engineering mechanics and student learning achievement in hydraulics courses. The technique used in data collection is documentation technique. The population in the research is all Civil Engineering students with a total of 22 people from the class of 2019 to the class of 2022. The results of the research show that testing the hypothesis obtained a correlation coefficient of r = 0.322 and determination r2 = 0.1103. These results indicate that 11.03% of the variation that occurs in learning achievement in the Hydraulics course is influenced by mastery of engineering mechanics. The magnitude of this qualitative determining power can be said to be still lacking, because students' learning achievement in hydraulics courses is influenced by the level of mastery of engineering mechanics by 11.03% while the remaining 88.97% is determined by other factors..